Comparison of the Inhibitory Effects of Clotrimazole and Ketoconazole against Human Carboxylesterase 2 - Zhao, Tingting; Wang, Dalong; Zhao, Shan; Chen, Jing; Dou, Tongyi; Ge, Guangbo; Wang, Changyuan; Meng, Qiang; Sun, Huijun; Liu, Kexin; Wu, Jingjing (Current Drug Metabolism, 2021)
Background: Both clotrimazole and ketoconazole have been verified to have an inhibitory effect on CYP3A4. hCE2 is an enzyme closely related to the side effects of several anti-cancer drugs. However, the interactions between hCE2, clotrimazole, and ketoconazole remain unclear. Objective: The objective of this study was to investigate and compare the inhibition behaviors of the two antifungal agents, ketoconazole and clotrimazole, on the human liver microsome hCE2 and to explore their underlying mechanism. Methods: The inhibitory effects were investigated in human liver microsomes (HLMs) using fluorescein diacetate (FD), N-(2-butyl-1,3-dioxo-2,3-dihydro-1H-phenalen-6-yl)-2-chloroacetamide (NCEN) and irinotecan (CPT- 11) as substrates of hCE2. Results: Clotrimazole significantly inhibited the hCE2 activity, which was manifested by attenuated fluorescence when the substrates were FD and NCEN. The inhibitory effect of clotrimazole towards hCE2 was much stronger than that of ketoconazole, and the inhibitory behaviors displayed substrate-dependent inhibition. The IC50 value of clotrimazole, with CPT-11 as the substate, increased by 5 and 37 times more than that with FD and NCEN, respectively. Furthermore, the inhibitions of clotrimazole towards hCE2-mediated hydrolysis of FD, NCEN, and CPT-11 were all in competitive mode with the Ki values of 0.483 μM, 8.63 μM, and 29.0 μM, respectively. Molecular docking result of clotrimazole binding to hCE2 illustrated that clotrimazole could efficiently orient itself in the Z site cavity of hCE2. Conclusion: Clotrimazole displayed a strong inhibitory effect against hCE2, which might be used as a potential combined agent co-administrated with CPT-11 to alleviate the hCE2-mediated severe side effects.
Keywords: drug-drug interaction